Level of blood glucose, fatigue and sexual anxiety in diabetes mellitus sufferers - Karyati, Sri; Kusumaningrum, Rafika Putri Ayu; Siswanti, Heny; Suwandi, Edi Wibowo (South East Asia Nursing Research, 2022)
Diabetes causes a decrease in glycogen which results in fatigue and neurovascular disorders which cause a decrease in body organ function. This condition raises their concerns about sexual problems in themselves and this is the main trigger for sexual problems in DM sufferers apart from physical problems. This study aims to determine the relationship between blood glucose levels and fatigue levels with sexual anxiety in diabetes mellitus sufferers. This research is correlational quantitative research with a cross-sectional time approach. The population of this study were DM sufferers in the Nalumsari Community Health Center working area with a sample of 36 people. The results of the analysis using the Spearman rho test obtained a P value of 0.000 so it can be concluded that there is a significant relationship between blood glucose levels and levels of fatigue and sexual anxiety in diabetes mellitus sufferers in the Nalumsari I Regional Health Center working area.